Aktywność turystyczna mieszkańców Wrocławia w weekendy - Dołęga, Arkadiusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The growing popularity of weekend tourism in Poland is caused by socioeconomic development of the country. The structure, model and characteristics of weekend excursions have changed lately. This paper contains results of researches that were carried out in Wrocław. The population living in agglomeration is the most typical weekend migration. Approximately 75 percent of the inhabitants of Wrocław went on a weekend trip. That fact proves a big role of weekend movement in a whole structure of tourism movement in Lower Silesia. Developing this part of tourism is crucial for tourism economy and communes in the region and has also its place in prepared "Tourism development programme in Lower Silesia". (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 190-200